Clinicopathologic and molecular analysis of embryonal rhabdomyosarcoma of the genitourinary tract: evidence for a distinct DICER1-associated subgroup - Kommoss, Felix; Stichel, Damian; Mora, Jaume; Esteller, Manel; Jones, David T. W.; Pfister, Stefan; Brack, Eva; Wachtel, Marco; Bode, Peter Karl; Sinn, Peter; Schmidt, Dietmar; Mentzel, Thomas; et al. (Modern pathology, 2021)
Embryonal rhabdomyosarcoma (ERMS) of the uterus has recently been shown to frequently harbor DICER1 mutations. Interestingly, only rare cases of extrauterine DICER1-associated ERMS, mostly located in the genitourinary tract, have been reported to date. Our goal was to study clinicopathologic and molecular profiles of DICER1-mutant (DICER1-mut) and DICER1-wild type (DICER1-wt) ERMS in a cohort of genitourinary tumors. We collected a cohort of 17 ERMS including nine uterine (four uterine corpus and five cervix), one vaginal, and seven urinary tract tumors. DNA sequencing revealed mutations of DICER1 in 9/9 uterine ERMS. All other ERMS of our cohort were DICER1-wt. The median age at diagnosis of patients with DICER1-mut and DICER1-wt ERMS was 36 years and 5 years, respectively. Limited follow-up data (available for 15/17 patients) suggested that DICER1-mut ERMS might show a less aggressive clinical course than DICER1-wt ERMS. Histological features only observed in DICER1-mut ERMS were cartilaginous nodules (6/9 DICER1-mut ERMS), in one case accompanied by foci of ossification. Recurrent mutations identified in both DICER1-mut and DICER1-wt ERMS affected KRAS, NRAS, and TP53. Copy number analysis revealed similar structural variations with frequent gains on chromosomes 2, 3, and 8, independent of DICER1 mutation status. Unsupervised hierarchical clustering of array-based whole-genome DNA methylation data of our study cohort together with an extended methylation data set including different RMS subtypes from genitourinary and extra-genitourinary locations (n = 102), revealed a distinct cluster for DICER1-mut ERMS. Such tumors clearly segregated from the clusters of DICER1-wt ERMS, alveolar RMS, and MYOD1-mutant spindle cell and sclerosing RMS. Only one tumor, previously diagnosed as ERMS arising in the maxilla of a 6-year-old boy clustered with DICER1-mut ERMS of the uterus. Subsequent sequencing analysis identified two DICER1 mutations in the latter case. Our results suggest that DICER1-mut ERMS might qualify as a distinct subtype in future classifications of RMS.
Gesehen am 14.12.2022